THE ROLE OF HABITUS IN DEVELOPING INTELLECTUAL CAPITAL STUDENT AT MA'HAD ALY AL FURQON, PONOROGO - Katni dan Anip Dwi Saputro (Universitas Muhammadiyah Ponorogo, 2017)
The institution always expects the output quality and personality, but if the surroundings of education never give appropriate habitus, then the result will not be achieved. On the basis of this research, trying to peel about the role of habitus in developing intellectual capital which is a student at Ma'had synergy between the structure with an agency, how an intellectual capital created and run in a Ma'had university. The question of the Islamic College during this time, when students are extremely variable input, its ability to be tough in the formation and determination of the standard of their abilities. The results of this study found that the role of habitus intellectual capital improvement done in Mahad Aly Al Furqon Ponorogo there are seven models of the structure that supports the students ' intellectual capital development in Ma'had Aly Al Furqon Ponorogo. As for overcoming the Burnout, the students do a variety of activities that make students fresh so avoid burnout. The results of the intellectual capital developed in the Mahad Aly Al Furqon students achieved the target of memorizing a set amount and the more intellectual growth of students marked with a creative, independent inquiries, in drawing up the scientific agenda, active removing the arguments in different ways.